Penggunaan sedasi inhalasi N 2 O-O 2 pada penatalaksanaan marsupialisasi ranula rongga mulut anak anxiety patient - Harun Achmad; Dini Safitri; Kirana Lina Gunawan (Journal of Dentomaxillofacial Science, 2008)
Inhalation sedation becomes the main choice in the dental treatment of children whoovercome have any kind of the fearness, concerned with pain in the treatment of theirteeth. Inhalation sedation with N2O-Ocauses sedation situation that accompanies byanalgesia to the conscious patients by inhaling the mixture of oxide nitrogen (N2O)with oxygen (O), that was known as psychosedation or concious sedation technique.Ranula is a mucocel that developed at the base of the mouth, unilateral, bluish, andthe shape like frog stomach. On this paper, will be esplained about N2O-O2inhalationsedation technique that concider the condition for the patient, using short time andcan be recovered immediately. A 9 year old girl diagnosed by ranula sublingualis onthe cavity of the mouth was very anxiety and fear in this treatment. The ranula treatedwith marsupialitation and was supervised by inhalation sedation of N2O-O2 in theSpecial Dental Care Hasan Sadikin Hospital Bandung. The result showed thatinhalation sedation with N2O-O2 was very very useful to reduce anxiety and fear tocertain patients with minimal side-effect. So it was very important to a dentist to knowthe selection of the patient, equipment and the technique of inhalation sedationadequately